Psycho-physical wellbeing as a technological-environmental design challenge - Angelucci, Filippo; Radogna, Donatella (Frontiers in Built Environment, 2024)
Introduction: In performance-based approaches and quality assessment protocols used both in the technological design of architecture and the environmental design of the built habitat, the concept of psycho-physical wellbeing is usually defined in purely quantitative human-techno-centric or eco-techno-centric terms. However, in socio-technical-environmental realities in continuous transition, wellbeing extends to areas that cannot be confined within the notions of comfort or healthiness because it involves material and immaterial, cultural and technical, aesthetic and performative, real and virtual aspects.Method: The aim of this article emerges from studies being conducted as part of Ex-Mind research. The working hypothesis is to broaden performance-based approaches in a technological-environmental sense to avoid reducing the goal of psycho-physical wellbeing just to the compliance with technical-constructive aspects. It could be possible combining the material and quantifiable dimensions with other aspects that extend the project to sensorial, perceptive, and emotional interactions. Important theoretical-scientific evidence is already emerging on this dichotomy to be overcome from areas of project evaluation responsive to the new paradigms of sustainability such as resilience, inclusive placemaking, and wellbeing according to the flourish model. Characteristics such as dimensions, proportions, shapes, colors, scents and immaterial aspects of spaces, for example, should be evaluated with respect to the complex physical and mental comfort conditions that they can produce.Results: In the technological-environmental vision of the human habitat project, the objective of psycho-physical wellbeing should be a function of the dynamic balance between the constantly evolving users’/inhabitants’ needs and the variability of context factors and agents. The concept of wellbeing therefore takes on a scalar and expanded declination. Considering the technological-environmental approach, a possible element of originality emerges in the integrated and balanced human-environmental centered vision aimed at broadening the framework of the qualitative-quantitative references of the project of the human habitat. This could be an alternative bio-psycho-socio-technological methodological vision starting from the determinants of wellbeing in a broad sense, including natural, cultural and socioeconomic environmental factors, social and collective networks of relationships and participation, individual behavioral, physical, and functional factors of people. Added to these determinants are the different technological-environmental interface systems with which the project is able to define, in a bio-psycho-socio-technological sense, multiple and variable regulatory conditions of wellbeing, at a building, urban, and territorial level.Discussion: The possible outcomes of this alternative and integrated hypothesis are related to the reconnection with the production and regeneration processes of the built material, to the reorganization and reinvention of spatial and perceptual relationships between individuals, communities, technologies, environment, and to the integration of non-directly quantifiable subjective variables into the design of the built environment. The proposed integrated bio-psycho-socio-technological vision may open for developments concerning the expansion of the determinants of psycho-physical wellbeing through new performative descriptors and the definition of agile tools, procedures, and metrics to integrate wellbeing assessments, including consensus-based approaches.